An Overview of Patients’ Sleep Quality in a Public Health Setting - Saida, Said Aandy; Cahyadi, Edy; Husna, Rozatul; Rizkidawati, Rizkidawati; Desreza, Nanda (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2025)
Sleep quality refers to the extent to which a person feels satisfied with their sleep, assessing whether the sleep they get is sufficient or not. This is important because each individual has various activities that affect their sleep needs. The Department of Health explains that sleep is part of the body's biological rhythm that helps restore the body's strength. The purpose of this study is to determine the distribution of age groups, gender, sleep quality components, and sleep quality frequency. This study is a descriptive observational study conducted at the Baiturahman Health Center in Banda Aceh and carried out in February 2025. The sample size in this study was 100 patients. The results showed that 39 respondents (39.0%) had good sleep quality, 36 respondents (36.0%) had a nighttime sleep duration of approximately 5 to 6 hours, and 40 respondents (40.0%) experienced difficulty falling asleep within 30 minutes. Sleep efficiency of 75-84% was recorded in 47 respondents (47.0%). Additionally, sleep disturbances with a score of 1 were reported by 60 people (60.0%). 92 respondents (92.0%) stated they had never used sleep medication. Meanwhile, 38 people (38.0%) showed daytime activity disturbances with a score of 1. Recommendations to the Community Health Center (Puskesmas) institution to further enhance efforts in providing information to the public about the importance of maintaining patient sleep quality to avoid illness.